(untitled) (Education in the 21st Century, 2025)
The problem under study is relevant, modern and has theoretical and practical significance. Because it is known that in the general system of upbringing, education and development of children with profound and partial visual impairments, the role and importance of education is immeasurably increasing today. At the same time, profound visual impairments in a child significantly complicate the organization and conduct of educational work in a public school, communication with them and teachers and classmates. Therefore, on the level of awareness of teachers who provided education, in matters of psychophysical features of the development of blind children, building and conducting educational work with them in the same class with normally seeing peers largely depends on the correct and effective education and development of blind children, preparing them for an active independent life. In recent years, the scientific and methodological literature has emphasized the importance of education for children with profound and partial visual impairments, the formation and development of the level of awareness of teachers who provide education for blind children in organizing and conducting educational work with them in the same class with normally seeing peers. At the same time, in the special scientific and methodological literature and in the practice of mass schools, the problem of improving the qualifications of teachers who provide education for blind children has not yet been given due attention. Whereas the solution to this problem is very significant, which is of great importance for blind children, their education, upbringing, general development and entry into an independent active life. Recognizing the importance of improving the qualifications of teachers on the specifics of integrative education for the entire category of visually impaired schoolchildren, this article focused on the problems of education only for blind children, that is, on that subcategory of children with visual impairment, which is the most difficult in terms of joint learning with normally seeing children Considering the foregoing, the article presents important aspects of professional development of teachers implementing education for blind children. On the basis of the presented material, a theoretical analysis of the issues under consideration was carried out, conclusions and practical recommendations were made that are necessary for teachers implementing education for blind children in organizing and conducting educational work with these children in the classroom where normally seeing peers study.